PENGARUH ORIENTASI KEWIRAUSAHAAN DAN ORIENTASI PASAR TERHADAP KEUNGGULAN BERSAING (Studi Pada Sentra IKM Tenun Ikat Troso Kabupaten Jepara) - Mia Eka Arianti; Sri Suryoko (Jurnal Ilmu Administrasi Bisnis, 2020)
This study purposed to determine the effect of entrepreneurial orientation and market orientation on competitive advantage. The research used explanatory research. The data was collected by questionnaire that used purposive sampling technic. 88 respondents were sample in this research who had been selected by specified criteria. Data analysis used validity, reliability, correlation coefficient, determination coefficient, simple and multiple linear regression, significance of the t test, and F test precessed by IBM SPSS version 21.0 program. The results showed that partially there was a positive effect on entrepreneurial orientation at competitive advantage and the positive effect on market orientation at competitive advantage; while simultaneously the positive effect on entrepreneurial orientation and market orientation at competitive advantage. The effect of entrepreneurial orientation on competitive advantage was greater than the effect of market orientation on competitive advantage. Suggestions in this research were crafters must increase courage in making decisions, take advantage of existing market opportunities with new innovations, increase references and create different motives from competitors so that products have their own characteristics and are not easily imitated by competitors so can increase competitive advantage in Medium Small Industry Tenun Ikat Troso.